The role of telemedicine towards improved sustainability in healthcare and societal productivity in Turkey. - Figen Özen; Alptug H Kaynar; A Kubilay Korkut; Melike Elif Teker Açıkel; Z Dilsun Kaynar; A Murat Kaynar (PLoS ONE)
The healthcare systems of low and middle-income countries suffer from lack of resources that could be remedied by employing novel care strategies such as telemedicine [1]. Here, the hypothetical impact of delivering telemedicine care on environment and society in three busy cardio-vascular clinics in Istanbul, Turkey, is examined. The study exploits demographics, wages, productivity, and patient-specific data to develop a hypothetical telemedicine framework for the Turkish healthcare landscape. Specifically, the distance traveled and travel time to receive care using location of the clinics and patients addresses seeking care are tabulated. Data from August 3, 2015, to January 25, 2023 involves 45,602 unique encounters with 448 unique diagnoses recorded for the patient encounters, where the patients in the top 5% of the most common diagnoses traveled 23.82 ± 96.3 km to reach the clinics. Based on our model, telemedicine care for cardiovascular diseases would have saved 656,258 km if all patients were to take the first visit in person followed by telemedicine visits in lieu of face-to-face care for all visits. The travel-associated carbon footprint and wage losses for in-person care is calculated and exploiting telemedicine could have saved approximately 30% carbon footprint and prevented approximately $503,752.8 wage loss. It is possible that telemedicine could ease the burden on patients, environment, increase access, and prevent the wage losses caused by unnecessary hospital visits.